Insights into the Cytoadherence Phenomenon of Plasmodium vivax: The Putative Role of Phosphatidylserine - Totino, Paulo Renato; Lopes, Stefanie Costa (Frontiers in Immunology, 2017)
Plasmodium vivax is the most geographically widespread and the dominant human malaria parasite in most countries outside of sub-Saharan Africa and, although it was classically recognized to cause benign infection, severe cases and deaths caused by P. vivax have remarkably been reported. In contrast to P. falciparum, which well-known ability to bind to endothelium and placental tissue and form rosettes is related to severity of the disease, it has been a dogma that P. vivax is unable to undergo cytoadherent phenomena. However, some studies have demonstrated that red blood cells infected by P. vivax can cytoadhere to host cells, while the molecules participating in this host-parasite interaction are still a matter of speculation. In the present overview we address the evidences currently supporting the adhesive profile of P. vivax and, additionally, discuss the putative role of phosphatidylserine – a cell membrane phospholipid with cytoadhesive properties that has been detected on the surface of Plasmodium-parasitized red blood cells.